The Role of Civil Society Organizations in Creating Conflict Resolution through Multicultural Education - Ahmad Saefudin (Islamic Studies Journal for Social Transformation, 2019)
Dermolo as one of the villages in Kembang, Jepara, was ever hit by a conflict under a religious background.This friction involved Islamic and Christian groups. The dispute between the two groups increasinglyculminated and seemed to have no end without the presence of the Nation. When the Regional Governmentof Jepara encountered a deadlock in breaking down this social conflict, the presence of a civil societyorganization was necessary. Lakpesdam NU Jepara since 2014 up to now has been trying to extinguishthe fire of conflict in Dermolo which was initially triggered by disputes over the use of a worship place.Through a qualitative descriptive approach by utilizing the theory of conflict resolution and multiculturaleducation, this paper finally succeeds in mapping the four multicultural education patterns used byLakpesdam NU. Those are economic empowerment, religious approaches, empowering women, andempowering village cadres. The result of this academic discourse at the same time provides an alternativemethodological offer that can be replicated by the stakeholders of the policymakers, for example, theRegional Government and the relevant Regional Apparatus Organization. It can be used as a prototype forcivil society organizations and peace activists in settling disputes wrapped in religious sentiment. This kindof inclusive pattern is considered as quite successful as a conflict resolution strategy. Lakpesdam NU Jeparais the only institution that has the sympathy of the residents and the Dermolo Government because it hascontributed positively to restoring social harmony between Christian and Islam groups.